ASDIN white paper: Assessment and management of hemodialysis access-induced distal ischemia by interventional nephrologists. Issue 5 (September 2020) - Beathard, Gerald A; Jennings, William C; Wasse, Haimanot; Shenoy, Surendra; Hentschel, Dirk M; Abreo, Kenneth; Urbanes, Aris; Nassar, George; Dolmatch, Bart; Davidson, Ingemar; Asif, Arif
Although not common, hemodialysis access-induced distal ischemia is a serious condition resulting in significant hemodialysis patient morbidity. Patients with signs and symptoms suggestive of hand ischemia frequently present to the general and interventional nephrologist for evaluation. In order to care for these cases, it is necessary to understand this syndrome and its management. Most cases can be managed conservatively without intervention. Some cases requiring intervention may be treated using techniques within the scope of practice of the interventional nephrologists while other cases require vascular surgery. In order for the interventional nephrologists to evaluate and manage these cases in a timely and appropriate manner, practice guidelines are presented.